2012
DOI: 10.1186/1476-511x-11-109
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic effect of polyunsaturated fatty acids (PUFAs) and its metabolites on brain-derived neurotrophic factor (BDNF) through molecular docking simulation

Abstract: BackgroundBrain-derived neurotrophic factor (BDNF) is a potent neurotrophic factor that is implicated in the regulation of food intake and body weight. Polyunsaturated fatty acids (PUFAs) localised in cell membranes have been shown to alter the levels of BDNF in the brain, suggesting that PUFAs and BDNF could have physical interaction with each other. To decipher the molecular mechanism through which PUFAs modulates BDNF’s activity, molecular docking was performed for BDNF with PUFAs and its metabolites, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…These results suggest that PUFAs and their metabolites especially, LXA 4 physically interact with BDNF. Similar interaction(s) was noted between BDNF and resolvins and protectins but were of lesser intensity compared to LXA 4 [111].…”
Section: Interaction Between Pufas and Bdnfsupporting
confidence: 77%
See 1 more Smart Citation
“…These results suggest that PUFAs and their metabolites especially, LXA 4 physically interact with BDNF. Similar interaction(s) was noted between BDNF and resolvins and protectins but were of lesser intensity compared to LXA 4 [111].…”
Section: Interaction Between Pufas and Bdnfsupporting
confidence: 77%
“…Such a study may pave the way to the development of custom made combinations of various PUFAs with or without BDNF to improve prognosis of patients with autism. Furthermore, significant interaction(s) depicted above between PUFAs/ lipoxins/resolvins/protectins and BDNF [111] also may have relevance in other neurologic/psychiatric conditions such as schizophrenia, Alzheimer's disease, Huntington's disease, and Parkinson's disease [136][137][138].…”
Section: Nitric Oxide In Autismmentioning
confidence: 99%
“…Indeed, it has been found that ω-3 PUFAs dietary deficiency might increase vulnerability to LPS-induced spatial memory impairment (Delpech et al, 2015). Furthermore, PUFAs may affect basal and stimulated production of serotonin (Kodas et al, 2004), regulate transport of antidepressants through BBB (Kuan et al, 2011) and increase the production of BDNF (Rao et al, 2007;Vetrivel et al, 2012). In turn, the effects of PUFAs on oxidative stress remain the matter of dispute regarding safety issues since pro-oxidative effects have been also reported (Di Nunzio et al, 2016).…”
Section: Polyunsaturated Fatty Acids (Pufas)mentioning
confidence: 96%
“…In this study, no significant effects of peripheral levels of Vascular Endothelial Growth Factor (VEGF) and IFN-γ on cognitive functioning were found. Indeed, eotaxin has been found to facilitate cognitive decline during aging by direct inhibition of adult hippocampal neurogenesis (Villeda et al, 2011). Interestingly, eotaxin undergoes a bidirectional transport through BBB that is mediated by binding to the blood cellular components in the slow phase and direct interactions with BBB in the rapid phase (Erickson et al, 2014).…”
Section: Other Cytokinesmentioning
confidence: 99%
“…Indeed, the hypothesis that PUFAs and their metabolites beneficially interact with BDNF and other neurotrophic factors has been recently suggested [36].…”
Section: Discussionmentioning
confidence: 99%